EVALUASI KESESUAIAN LAHAN DAN ARAHAN PEMUPUKAN N, P, DAN K DALAM BUDIDAYA TEBU UNTUK PENGEMBANGAN DAERAH KABUPATEN TULUNGAGUNG - Mulyono, Daru (Jurnal Sains dan Teknologi Indonesia, 2009)
The objectives of the research are to evaluate the suitability of land for sugarcane growth and give recommendation through land fertilization for optimal sugarcane cultivation. Furthermore, the impacts of this action are to increase the planting area of sugarcane and productivity. The research use GeographicalInformation System (GIS) in Tulungagung Regency, starting from June until October 2004. The results of the research showed that the suitable, conditionally suitable, and not suitable land for sugarcane cultivation in Tulungagung Regency reach to a high of 45,651 ha, 61,547 ha, and 6,038 ha respectively. Based on the soil condition with low contents of N, P and K, the dosage calculation of N, P, and K fertilizers for optimal sugarcane cultivation reach to a high of: N (ZA) = 500 kg/ha, P (SP-36) = 215 kg/ha, and K (KCl) = 260 kg/ha.